High school ninth Grade students' awareness and preferences for the cultural content of the EFL textbooks: a case in Turkey - Danacı, Seda. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis investigates the cultural content of an EFL textbook (i.e. The New English File Elementary) and high school ninth grade students’ awareness of and preferences for the cultural content of this textbook. The study consists of two parts. The first part involves content analysis of the textbook in question. In this part, pictures and reading texts of the book are searched for cultural elements. In this study, culture is examined in terms of target language culture, local culture, international culture and other countries’ cultures. The definition of culture adopted by the study involves four senses of culture (aesthetic, sociological, semantic and sociolinguistic) by Adaskou, Brittten and Fahsi (1990). The content of ‘culture’ concept in the study was determined with a pilot study. The second part of the study involves the investigation of the opinions of high school students with respect to their awareness of and preferences for the cultural content of their EFL textbook. High school ninth grade students from an Anatolian high school in İstanbul, Turkey participated in the study. Data are collected through questionnaires and interviews. Results of the study revealed that the textbook in question represented the international culture and the sociological sense of culture in general. Results of the questionnaire and interviews conducted with the students indicated that participants were highly aware of the origin of the cultural elements in their EFL textbook. Results showed that students were more aware of the origin of cultural elements reflecting the sociological sense of culture while more content with the ones reflecting the aesthetic sense of culture. Results of the questionnaire about their preferences for the cultural content of an EFL textbook revealed that students wanted to see topics about social life more frequently. Most of the students having participated in the interviews stated that they liked the textbook “The New English File Elementary”, target language culture and international culture were represented in the textbook while local culture was not, they would like to change the book and add topics about the local culture. In sum, this study suggests preparing ELT textbooks and materials for a specific group of learners by taking their local culture and preferences into consideration.
Keywords: English language -- Textbooks for foreign speakers.